#gagalkanomnibuslaw movement: How Simulacra Sparks Mass Action - Oktavianingtyas, irmawati; Wono, Hilda Yunita; Gusfa, Henni (Bricolage : Jurnal Magister Ilmu Komunikasi, 2023)
The hash-tag #gagalkanomnibuslaw used by the twitter "social media '' users appears as a form of virtual protest of Indonesian people aiming at the Indonesian government. Information about  Omnibus Law (UU Cipta Kerja) has been growing rapidly on social media since the popularity of the hash-tag increased. Unfortunately, the popularity of this hash-tag has made various information without references (hoaxes) which further confuses the original essence of the Movement. Based on that, The overall study objective is to find out how the false reality created by the hash-tag #gagalkanomnibuslaw is able to move the mass. This is a qualitative study using Jean Baudrillard’s concept of simulacra to analyze the case. The result shows that the participants of the movement were trapped in simulacra, where the false reality of the information in cyberspace was used as a reference in carrying out both virtual and nonvirtual protest.